1980
DOI: 10.1007/bf01246144
|View full text |Cite
|
Sign up to set email alerts
|

Anterior interosseous-nerve paralysis as a complication of supracondylar fractures of the humerus in children

Abstract: Two cases of anterior interosseous nerve syndromes following supracondylar fractures of the humerus in children are reported. In both cases spontaneous recovery began at 8 weeks and was complete at 10 weeks. The syndrome is discussed and the literature reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Anterior interosseous nerve paralysis as a complication of supracondylar fractures of the humerus in children has been described in several studies. [3][4][5]8,10,11,15,16,20,21,34 Fascicular torsion of the AIN in three patients with nontraumatic AIN palsy was described by Yasunaga, et al 39 Each of the three patients had an AIN that intraoperatively showed hourglass-like constrictions and 30˚ of fascicular torsion. These abnormalities were believed to have been formed on branching of the AIN from the median nerve.…”
Section: Origins Of Ain Entrapment or Injury Syndromementioning
confidence: 92%
“…Anterior interosseous nerve paralysis as a complication of supracondylar fractures of the humerus in children has been described in several studies. [3][4][5]8,10,11,15,16,20,21,34 Fascicular torsion of the AIN in three patients with nontraumatic AIN palsy was described by Yasunaga, et al 39 Each of the three patients had an AIN that intraoperatively showed hourglass-like constrictions and 30˚ of fascicular torsion. These abnormalities were believed to have been formed on branching of the AIN from the median nerve.…”
Section: Origins Of Ain Entrapment or Injury Syndromementioning
confidence: 92%